High‐Throughput Screening to Identify Compounds That Increase Fragile X Mental Retardation Protein Expression in Neural Stem Cells Differentiated From Fragile X Syndrome Patient‐Derived Induced Pluripotent Stem Cells. (21st May 2015) - Kumari, Daman; Swaroop, Manju; Southall, Noel; Huang, Wenwei; Zheng, Wei; Usdin, Karen
Abstract : Fragile X syndrome (FXS), the most common form of inherited cognitive disability, is caused by a deficiency of the fragile X mental retardation protein (FMRP). In most patients, the absence of FMRP is due to an aberrant transcriptional silencing of the fragile X mental retardation 1 ( FMR1 ) gene. FXS has no cure, and the available treatments only provide symptomatic relief. Given that FMR1 gene silencing in FXS patient cells can be partially reversed by treatment with compounds that target repressive epigenetic marks, restoring FMRP expression could be one approach for the treatment of FXS. We describe a homogeneous and highly sensitive time‐resolved fluorescence resonance energy transfer assay for FMRP detection in a 1, 536‐well plate format. Using neural stem cells differentiated from an FXS patient‐derived induced pluripotent stem cell (iPSC) line that does not express any FMRP, we screened a collection of approximately 5, 000 known tool compounds and approved drugs using this FMRP assay and identified 6 compounds that modestly increase FMR1 gene expression in FXS patient cells. Although none of these compounds resulted in clinically relevant levels of FMR1 mRNA, our data provide proof of principle that this assay combined with FXS patient‐derived neural stem cells can be used in a high‐throughput format to identify better lead compounds for FXS drug development. Significance: In this study, a specific and sensitive fluorescence resonance energy transfer‐based assay for fragile X mental retardation protein detection was developed and optimized for high‐throughput screening (HTS) of compound libraries using fragile X syndrome (FXS) patient‐derived neural stem cells. The data suggest that this HTS format will be useful for the identification of better lead compounds for developing new therapeutics for FXS. This assay can also be adapted for FMRP detection in clinical and research settings. Abstract : A homogeneous and highly sensitive time‐resolved fluorescence resonance energy transfer assay for fragile X mental retardation protein (FMRP) detection is described. Approximately 5, 000 known tool compounds and approved drugs were screened using this FMRP assay. The data provide proof of principle that this assay combined with fragile X syndrome (FXS) patient‐derived neural stem cells can be used in a high‐throughput format to identify better lead compounds for FXS drug development.